The Methods of Determination of Settlement’s Electricity Self-Sufficiency - Kulcsár, Balázs (International Journal of Engineering and Management Sciences, 2018)
The Idea of the Energy Change became in available proximity with the technological development. The change from the fossil energy to the renewable energy sources is a question of the territorial extension’s question now, so the change is available on settlement, regional, or global level. This study analyses the method of those settlement systems, which achieved the 100% renewable energy systems. It categorizes the methods which lead to the all renewable energy supply based system and the current study examines the self-sufficiency level of the Hungarian settlements through the international organizations and case studies and applying its own methods.